Characterization of distensibility, plaque burden, and composition of the atherosclerotic carotid artery using magnetic resonance imaging - Cantón, Gádor; Hippe, Daniel S.; Sun, Jie; Underhill, Hunter R.; Kerwin, William S.; Tang, Dalin; Yuan, Chun (Medical physics (Lancaster), 2012)
Purpose: Arterial distensibility is a marker that can measure vessel wall functional and structural changes resulting from atherosclerosis with applications including estimation of mechanical properties of the wall. We sought to assess the feasibility of using magnetic resonance imaging (MRI) to include wall distensibility in the characterization of atherosclerotic carotid arteries and to analyze the relationship between distensibility and morphological and compositional plaque features. Methods: Five healthy volunteers were imaged with a multiple-slice CINE MR sequence twice, within 24 h, to determine the interscan reproducibility of distensibility measurements. Twenty-one subjects with >15% carotid stenosis and the five healthy volunteers were imaged using a multicontrast carotid MRI protocol to characterize arterial wall morphology and composition. Normalized wall index (wall area/total vessel area), maximum wall thickness and, if present, percentages of wall area occupied by calcification and lipid-rich necrotic core were determined. A multiple-slice CINE MR sequence was added to the multicontrast protocol to measure the distensibility coefficient (DC) at several locations spanning the bifurcation. The intraclass correlation coefficient (ICC) and the coefficient of variation were used to assess the reproducibility of DC measurements made on the healthy subjects. The DC was compared between arterial segments and between the healthy and diseased groups. Furthermore, within the diseased group, DC was correlated to plaque morphology and composition at each location as well as that averaged over the plaque. Results: Distensibility measurements were highly reproducible: ICC (95% confidence interval) was 0.998 (0.96–1.0) for the common carotid segment and 0.990 (0.92–1.0) for the internal carotid segment. In healthy volunteers, we found significantly higher distensibility in the common segment of the carotid artery compared to the internal carotid segment (mean ± SD = 4.56 ± 1.02 versus 3.56 ± 1.32 × 10−5/Pa; p < 0.05). However, no segmental differences were seen in the diseased group (3.25 ± 1.84 versus 3.26 ± 1.60 × 10−5/Pa; p = 0.607). Location-to-location changes in DC were not found to correlate to changes in the local plaque morphology or composition nor were average DC found to be associated with aggregate plaque features. Conclusions: These results demonstrate the feasibility of MRI to measure distensibility in the carotid artery and to presumably detect changes in distensibility due to age and/or disease. The results suggest that the effect of atherosclerosis on local distensibility may not strongly depend upon the specific underlying plaque features in mild to moderate stenotic carotid lesions though more diffuse or nonlocal changes in arterial distensibility could not be ruled out.